Teaching NeuroImage: Primitive Drainage Pattern of Basal Vein of Rosenthal: An Underrecognized Cause of Perimesencephalic Subarachnoid Hemorrhage. (19th July 2022) - Melanis, Konstantinos; Stefanou, Maria-Ioanna; Tsantzali, Ioanna; Tsomaka, Efi; Chondrogianni, Maria; Bakola, Eleni; Andreadou, Elizabeth; Lachanis, Stefanos; Tsivgoulis, Georgios
Abstract : A previously healthy 43-year-old man presented with coital thunderclap headache. A brain CT scan revealed a perimesencephalic subarachnoid hemorrhage (PMSAH). Digital subtraction angiography (DSA) showed a severe basilar artery vasospasm without underlying aneurysm (Figure 1). Under nimodipine treatment, the vasospasm resolved gradually. At a 1-month follow-up, a high-resolution (3T) MRI (HR-MRI) uncovered a primitive left basal vein of Rosenthal (BVR) draining to the lateral mesencephalic veins instead of the Galenic system. 1